The Efficacy of an Intermaxillary Skeletal Fixation after a Sagittal Splitting Ramus Osteotomy for Skeletal Open Bite - OGURA, MIKINOBU; SAKODA, SUMIO; SHIBA, RYOSUKE (Nihon Gaku Henkeishō Gakkai zasshi, 1994)
Orthognathic surgery for skeletal open bite is considered to be one of the most operations with relapse. To prevent postoperative relapse of the mandibular position, we tried to make intermaxillary skeletal fixation (IMSF) after sagittal splitting osteotomy of the mandibular rami, and compared it with a usual method of intermaxillary dental fixation (IMDF). IMSF was applied in 3 cases, and IHDF was applied in2cases. Lateral cephalograms were compared between the2groups before surgery, immediately, 6months, and one year after surgery. The later relapse of the mandibular position was significantly smaller in the IMSF group than in the IMDF group. IMSF was considered to be a useful method for postoperative fixation in the case of skeletal open bite.